Visual related quality of life after ICL V4c implantation in high myopia patients: a mini review - Zhao, Huailan; Zhu, Siquan (Frontiers in Medicine, 2025)
High myopia (≥ − 6.00 D) poses significant challenges to visual function and quality of life, with implantable collamer lens (ICL) V4c implantation emerging as a pivotal treatment. This mini review synthesizes evidence on visual-related quality of life (VRQoL) following ICL V4c implantation, focusing on predictability, objective/subjective visual quality, and complications. ICL V4c demonstrates long-term safety and efficacy, with safety indices (postoperative best-corrected visual acuity/preoperative best-corrected visual acuity) of 1.01–1.10 and efficacy indices (postoperative uncorrected visual acuity/preoperative best-corrected visual acuity) exceeding 0.90 over 5 years. Objective metrics, including higher-order aberrations and intraocular scattering, remain stable or improve postoperatively, while subjective outcomes show high patient satisfaction despite common but mild issues like halos (90.1% incidence) and glare (66.7% incidence). Complications such as cataract (1.7–6.8% incidence), corneal endothelial cell loss (≤5.7% over 8 years), and ICL malposition are rare and often manageable. While axial length progression in super-high myopia requires monitoring, ICL V4c remains a robust option for enhancing VRQoL in high myopia patients. Future research should prioritize large-scale, long-term studies to validate outcomes and optimize surgical protocols.